2014
DOI: 10.1128/iai.00096-14
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Promotes Neutrophil Extracellular Trap Formation in Pulmonary Aspergillosis

Abstract: f NADPH oxidase is a crucial enzyme in antimicrobial host defense and in regulating inflammation. Chronic granulomatous disease (CGD) is an inherited disorder of NADPH oxidase in which phagocytes are defective in generation of reactive oxidant intermediates. Aspergillus species are ubiquitous, filamentous fungi, which can cause invasive aspergillosis, a major cause of morbidity and mortality in CGD, reflecting the critical role for NADPH oxidase in antifungal host defense. Activation of NADPH oxidase in neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 67 publications
2
104
1
1
Order By: Relevance
“…The anti-fungal activity of NETs has been attributed to CP in Candida albicans dermal abscess and intranasal infection models and in vitro in response to Aspergillus nidulans (37, 38). NETs have been identified in lungs of A. fumigatus infected mice (39, 40); however, rather than using resting conidia as used in the current study and which are the form that is normally inhaled and phagocytosed, those reports instilled the lungs with conidia that had been previously incubated for 7h, or with hyphal fragments. Although we are investigating NET formation during fungal corneal infection, those studies and ours indicate that CP, and therefore CP-laden NETs, are important to regulate growth of extracellular hyphae rather than conidia.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-fungal activity of NETs has been attributed to CP in Candida albicans dermal abscess and intranasal infection models and in vitro in response to Aspergillus nidulans (37, 38). NETs have been identified in lungs of A. fumigatus infected mice (39, 40); however, rather than using resting conidia as used in the current study and which are the form that is normally inhaled and phagocytosed, those reports instilled the lungs with conidia that had been previously incubated for 7h, or with hyphal fragments. Although we are investigating NET formation during fungal corneal infection, those studies and ours indicate that CP, and therefore CP-laden NETs, are important to regulate growth of extracellular hyphae rather than conidia.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that some neutrophils were capable of performing NETosis although exhibiting osmotic swelling requires further attention in future research, but has in part been investigated by Ting-Beall et al (49), who reported that neutrophils can tolerate a certain range of osmolalities and regulate their volume in response to osmotic stress. Importantly, it is known that NETosis occurs only under conditions where oxygen is present and that the enzyme NADPH-oxidase, which requires oxygen to form ROS, is required for NET formation (34, 50). Therefore, it can be concluded that in an oxygenated setting, some neutrophils mount ROS-mediated defences to A. actinomycetemcomitans , while others are lysed by Ltx.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical inducers such as PMA, LPS and microbes ( S. aureus and Aspergillus sp .) that induce NETs are NADPH oxidase dependent and are abrogated upon pharmacological inhibition of the enzyme284142. Mutations in gene(s) coding for NADPH oxidase subunit proteins leads to chronic granulomatous disease and these patients fail to make NETs43.…”
Section: Discussionmentioning
confidence: 99%